Dramatic Perezhivanie as a driver of executive functions development through role-play in early childhood: Theoretical framework and experimental evidence - Sukhikh, Vera L.; Veresov, Nikolay N.; Veraksa, Nikolay E. (Frontiers in Psychology, 2022)
Role play in early childhood is associated with development of executive functions (EFs), although study results remain inconsistent. Due to the complex nature of the role play the underlying mechanisms of these associations are not obvious. In this article play is viewed in the framework of the cultural-historical approach as a special social situation that can become the social situation of development if it results in dramatic perezhivanie of a child. In this study we compared the level of EFs and play behavior between two play contexts: play guided by an adult and one with less adult involvement. Play behavior was analyzed based on five behavioral measures suggested to be the markers of dramatic perezhivanie. Measures of EFs were taken before and after the experimental procedure. Results show that dramatic perezhivanie might be considered as a driver of EFs development through role play in early childhood. As well as this, the involvement of an adult into play was associated with different patterns of EFs dynamics before and after the intervention. Future work can investigate if the construct of dramatic perezhivanie, microsocial situation of development and micro-crisis might explain variability of the study results on the association between the role play and child development.